1976
DOI: 10.1071/ch9761605
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium(IV) carboxylates

Abstract: Zirconium(~v) carboxylates, Zr(OOCR)4 where R = Me, Et, CHZCl, CHCl, and CCI,, have been prepared by the reaction of zirconium(~v) chloride and carboxylic acids. The compounds have been characterized by elementary analyses, thermogravimetry and infrared spectral data. The compounds are non-electrolytes in nitrobenzene and probably have polymeric structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…42 However, this salt is prone to hydrolysis. 44,45 The results of this study showed that, regardless of saliva Phosphate-based end of 10-MDP forms a bond with zirconia whereas methacrylate-based end forms a bond with resin cements. 46 It was suggested that 10-MDP containing primer applied on zirconia would expose the hydrophobic methacrylate ends of the bound 10-MDP molecules which would increase the hydrophobicity of the zirconia surface.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…42 However, this salt is prone to hydrolysis. 44,45 The results of this study showed that, regardless of saliva Phosphate-based end of 10-MDP forms a bond with zirconia whereas methacrylate-based end forms a bond with resin cements. 46 It was suggested that 10-MDP containing primer applied on zirconia would expose the hydrophobic methacrylate ends of the bound 10-MDP molecules which would increase the hydrophobicity of the zirconia surface.…”
Section: Discussionmentioning
confidence: 71%
“…ZP forms a carboxylate salt through ionization of carboxylic acids upon application on Y‐TZP surface . However, this salt is prone to hydrolysis . The results of this study showed that, regardless of saliva contamination, cleansing with ZP significantly improved bond strength of SAC to zirconia surfaces ( P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely used precursors for the synthesis of zirconia may be zirconium acetate-based ones [8][9][10][11][12][13]. For example, zirconium tetraacetate can be prepared by the reaction of zirconium tetrachloride with an excess of acetic acid at 80 ∘ C [8]. Refluxing the mixture to the boiling point produces the formation of zirconium oxyacetate [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The latter can be prepared straightforwardly by the reaction of sodium carboxylate with an aqueous solution of a zirconium salt [7], leading to the linking of zirconium cations to the carboxylate anions. One of the most widely used precursors for the synthesis of zirconia may be zirconium acetate-based ones [8][9][10][11][12][13]. For example, zirconium tetraacetate can be prepared by the reaction of zirconium tetrachloride with an excess of acetic acid at 80 ∘ C [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation